Inversion and Fronting in Journalistic Style - Benová, Andrea (Univerzita Pardubice, 2016)
This thesis is devoted to a morphosyntactic and pragmatic analysis of inversion and fronting distributed in contemporary British newspapers. The theoretical part focuses on a description of the two aforementioned highlighting structures. In addition, word order and the principles of structuring information in a sentence are discussed. The analytical part subsequently studies the morphosyntactic features, function and occurrence of inversion and fronting in newspaper discourse.
Keywords: inverze; syntaktická prepozice; slovosled; principy; réma; téma; novinový styl; inversion; fronting; word order; principles; rheme; theme; journalistic style